1997
DOI: 10.1063/1.474685
|View full text |Cite
|
Sign up to set email alerts
|

Empirical potential energy surface for Ar⋅SH/D and Kr⋅SH/D

Abstract: High resolution electronic spectroscopy and an empirical potential energy surface for NeSH/D J. Chem. Phys. 110, 5065 (1999); 10.1063/1.478395High resolution electronic spectroscopy of KrOH/D and an empirical potential energy surface Experimental data from vibrationally and rotationally resolved laser induced fluorescence experiments have been used to produce potential energy surfaces ͑PES͒ for the excited à 2 ⌺ ϩ states of the Ar•SH and Kr•SH van der Waals complexes. This was done using a potential energy fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Also shown is an experimental spectrum from Ref. 20. The spacings between the peaks in the calculated Ar-SH spectrum are consistently ϳ5% smaller than in experiment.…”
Section: Intensities and Lifetime Factorsmentioning
confidence: 90%
See 2 more Smart Citations
“…Also shown is an experimental spectrum from Ref. 20. The spacings between the peaks in the calculated Ar-SH spectrum are consistently ϳ5% smaller than in experiment.…”
Section: Intensities and Lifetime Factorsmentioning
confidence: 90%
“…It is known that the presence of the Ar atom blocks the electronic predissociation of the SH radical, leading to a greatly increased lifetime of up to 600 ns for low-lying bound levels, compared to ϳ1 ns for the uncomplexed species. 20,50 However, the actual lifetime depends on the degree of vibrational excitation, and lifetimes specific to particular levels have been calculated by McCoy. 50 The top panel of Fig.…”
Section: Intensities and Lifetime Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique was first introduced by Pendergast et al [21] in the 2D surface eigenfunction calculations needed by the APH hyperspherical coordinate approach by Parker and Pack [22]. Recently Korambath et al [13] have found that this implicit SDT transformation to be effective for rovibrational eigen problems using sequential computers and Wu and Hayes [23] have applied the implicit SDT technique to obtain the HO 2 rovibrational energy levels on a CRAY T3D.…”
Section: Sequential Diagonalization and Truncationmentioning
confidence: 97%
“…Van der Waals molecules have received a good deal of attention recently because of the wealth of high resolution spectroscopic and dynamical data that is becoming available for these weakly bonded molecules [7][8][9][10][11][12]. Previously we reported rovibrational energy calculation using serial algorithms for van der Waals molecule such as Ar-HS, Kr-HS [13], Ar-HCl, and Ar-HO [14]. The Ar-HO molecule was selected for this study to generate detailed performance information that is typical for these atom-diatom van der Waals molecules.…”
Section: Introductionmentioning
confidence: 99%